Metformin versus insulin in gestational diabetes mellitus: a systematic review - Giovanna Noronha Berti; Igor Gutschov Oviedo Garcia; João Pedro Ruas Floriano de Toledo; Júlia Rodrigues Tatemoto; Lais Watanabe Marino; Mariana de Medeiros Legori; Sérgio Floriano de Toledo (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: The aim of this study is to assess the use of metformin with or without insulin for the treatment of Gestational Diabetes Mellitus compared to insulin alone. Data sources: This article consists of a systematic review of randomized clinical trials. The searches were carried out on MEDLINE including 7 studies, between 2010 to 2021. Study selection: Randomized clinical trials comparing metformin and insulin written in English, Spanish or Portuguese, with no time limit, were included. Data collection: Data was extracted from all the 7 articles and compared statistically when possible. Whenever data was not available or couldn't be statistically compared, the main results were described in detail. Data synthesis: Insulin alone is not superior than metformin with or without insulin on gestational diabetes mellitus. Conclusion: There is a potential viability of using metformin as an alternative compared to insulin alone in the treatment of Gestational Diabetes Mellitus. However, all assessed outcomes have a very low level of certainty of evidence and more studies are necessary to support these findings.